Tax reform in Brazil: a chance for fiscal justice and sustainability - Roberto Muhájir Rahnemay Rabbani; Allívia Rouse Carregosa Rabbani; Emilia Rahnemay Kohlman Rabbani; Gabriela Narezi (Revista de Direito Econômico e Socioambiental, 2024)
The Brazilian government has chosen a reformist approach regarding the raising of public funds. Society is often called upon to bear expenses that exceed its economic capabilities when faced with socioeconomic crises. This situation is worsened when public policies repress economic development and call on the poorer social classes to pay for public expenditures to maintain the status quo of the most privileged. At the current juncture, several factors affect the economic performance of a country, including environmental issues. Brazil stands out on these issues, as its biodiversity is one of the highest on the planet. This study analyzes the need for tax reform in Brazil that takes environmental policies into account, a strategy that has been used successfully by economically developed countries. The objective is to verify the socioeconomic profile of Brazil and map its current tax system, demonstrating the characteristics that determine if it is a progressive or regressive system. Based on this analysis, a simplified form of taxation is proposed that can provide greater social benefit and is more beneficial and effective than retrograde labor reforms. Finally, it demonstrates the feasibility of establishing a new foundation for Brazilian taxation, based on environmental steering taxes to promote sustainability.